Transport Infrastructure Planning: Assessment of Strategic Mobility by Use of the POINTER Impact Model. - Kronbak, Jacon; Leleur, Steen (Proceedings from the Annual Transport Conference at Aalborg University, 2002)
When evaluating large infrastructure projects one point to be made is the importance of supplementing the more traditional effects captured by a cost-benefit analysis as presented for example by use of the benefit cost ratio (BCR) with strategic effect modelling to obtain a more comprehensive view of the societal importance of the examined project. The focus of this paper is to present the first results of a comparison of the use of a strategic impact measurement (the POINTER index) for road traffic on the Great Belt Link, the Øresund Link and the proposed Fehmarn Belt link. Specifically a number of calculation scenarios have been made to assess the possibility of the POINTER approach to indicate the changes in strategic mobility (accessibility) associated with the implementing of one or more of the three fixed links. Finally, conclusions and a research perspective are outlined.